Heavy metal content and potential health risk of geophagic white clay from the Kumasi Metropolis in Ghana. (2016) - Nkansah, Marian Asantewah; Korankye, Mavis; Darko, Godfred; Dodd, Matt
Abstract: Geophagia is the craving for non-food substances and commonly practiced among pregnant women and children. Consumption of geophagic clay samples can have serious implications on the health of the consumers as a result of the presence of toxic metals such as Pb, As, Hg and Cd. This study sought to determine the levels of heavy metals in the studied geophagic clay samples and to determine the potential risks of heavy metals as cumulative carcinogenic and non-carcinogenic risks to the health of the consumers via oral (ingestion) and dermal exposure routes. A total of thirty (30) white clay samples were analysed using Niton Thermo scientific XRF Analyser (Mobile Test S, NDTr-XL3t-86956, com 24). The clay samples were found to contain essential elements such as Ca, Fe, K and Zn as well as toxic metals such as As and Pb. There were isolated cases of the presence of Hg and all samples had Cd levels below detection. Health risk indices such as hazard quotient and cancer risk were calculated and the results indicated that consumers are likely to suffer from cancer through ingestion of geophagic clay. Bioaccessibility studies were done on zinc and it did not indicate any potential toxicity due to zincs essential nature. The levels of heavy metals in some of the geophagic clay consumed by some residents in the Kumasi were high compared to the Permitted Maximum Tolerable Daily Intake (PMTDI) by (WHO/FAO) and may pose potential health threat over time.